Method to assess the potential of photovoltaic panel based on roof design - Abdi Gunawan Djafar; Yasin Mohamad (Institute of Advanced Engineering and Science, 2022)
The photovoltaic (PV) panel makes it possible for everyone to produce electricity in their own house. However, the panel is quite a costly investment and requires much consideration to maximize its potential. The roof has variables that would impact electricity generation. The roof of housing in Indonesia was built generally in a complex shape, a combination of gable and hip roofs. This research is conducted to break down factors affecting PV productivity in regard to the roof’s aspects. A computer simulation using Ladybug plugin in Rhinoceros software has been done to achieve the target. Initially, the performance of PV panels on the gable, and hip roof, is analyzed respectively. It is found that the roof’s slope, and orientation, contribute more to the amount of electricity produced than the shape itself. These factors were used to assess the PV potential in several housing models employing simple and complex roof (more than 2 surfaces) construction in the city of Gorontalo. Eventually, a comparison between the estimation of real PV production on housing, and the estimation provided by the simulation is conducted to verify the assessment method. The difference is about 4%, as proof the simulation result is reliable.